Partnership As An Effort To Care For Hypertension Through A Healthy Lifestyle - Darwis; Febryanti, Ade; Ervina, Lissa; Sakdiah, Ummu (CV Media Inti Teknologi, 2024)
Kelurahan Sukamerindu as the location of community service. This is because Kelurahan Suka Merindu is classified as slums, densely populated, cases of hyprtension and diabetes mellitus are high compared to other villages. Lurah, health devices and cadres actively participate in health programs. The purpose of community service activities is the implementation of case discovery activities, management and prevention of hypertensive patients in Bengkulu. Community service activities are carried out by registration and blood pressure checks, which are attended by 42 people. Furthermore, gymnastics activities in the form of healthy heart exercises, elderly exercises and Germas exercises, from the results of measurement of blood pressure found one grade hypertension with blood pressure 140-159 /90-99 mmHg as many as 15 people (35.7%). Counseling activities carried out by the lecture method followed by discussion and question and answer. Through community service activities, they know how to prevent hypertension through watermelon juice and know the benefits and can consume their own juice at home. Health socialization and promotion about the prevention and prevention of hypertension must be continued and can be an example for other villages and can be developed against the prevention and prevention of other non -communicable diseases, especially diabetes mellitus.